Methodik zur produktionsorientierten Produktanalyse für die Wiederverwendung von Produktionssystemen - 2REUSE : Konzept, Informationsmodell und Validierung am besonderen Beispiel des Karosserierohbaus in der Automobilindustrie - Stanev, Stilian (KIT Scientific Publishing, 2018)
Objective of this work is to ensure the basic manufacturability of a design for a predefined production line. The alignment between product and production line is the main factor for high quality and efficient change management before starting production. Main principal is: Do it right the first time. An efficient feedback process ensures that the relevant requirements from the later phase of the product development process are delivered in early stages of product design.
German
Keywords: PLM; information management; Automobilindustrie; Produktionsgerechte Produktentwicklung; Informationsmanagment; production oriented product development